Glycosylated siglec6 expression in syncytiotrophoblast-derived extracellular vesicles from preeclamptic placentas - White, K; Tannetta, D; Kandzija, N; Motta-Mejia, C; Gill, M; Zhang, W; Cooke, W; Thammasate, B; Cerdeira, S; Ri, R; Redman, C; Vatish, M (Elsevier, 2018)
Preeclampsia (PE) is associated with an exaggerated maternal systemic inflammatory response. The placenta releases extracellular vesicles from its syncytiotrophoblast layer (STBEV) into the maternal circulation. Expression of Siglec6, a transmembrane receptor of molecular weight 50kDa, is known to be upregulated in PE placental lysate (PL). Here we investigate the abundance of Siglec6 in STBEV, and whether the levels are different between PE and normal STBEV.